Active learning vs traditional education: social representations of Computer Science students. - Lozano González, Elí Orlando; Paparisteidi, Nefeli (Humanities & Social Sciences Communications, 2025)
This article examines the social representations of Computer Science students at EPITECH, a private institution in France specializing in Computer Science and focusing on active learning. The research centers on pedagogical assistants—advanced students at EPITECH—investigating their perceptions and attitudes toward educational approaches. EPITECH's model, which prioritizes project-based learning over traditional courses and professors, significantly influences students' social representations of pedagogical methods. The research adopts a qualitative approach, employing questionnaires and interviews with EPITECH pedagogical assistants. Findings reveal a preference for active learning due to its practical problem-solving capabilities. However, concerns are raised regarding the limited emphasis on reflective processes and critical thinking. Expert opinions underscore the necessity of incorporating multidisciplinary elements and ethical considerations into active learning, highlighting its strengths, virtues, and limitations compared to traditional education. In summary, the research provides valuable insights into the nuanced preferences and challenges faced by Computer Science students, emphasizing the importance of a balanced educational approach. Furthermore, the article contributes to a deeper understanding of social representations of educational models within the ever-evolving landscape of higher education.